The effect of forging texture and machining parameters on the fatigue performance of titanium alloy disc components. (January 2021) - Suárez Fernández, D.; Wynne, B.P.; Crawforth, P.; Fox, K.; Jackson, M.
Graphical abstract: Highlights: Fatigue performance variations have been analysed in Ti-6246 compressor disc material. Crack behaviour mechanisms have been linked to forging stages and machining processes. Billet regions subjected to lower strain during forging showed longer fatigue life. Machining processes have been found beneficial inhibiting crack initiation mechanisms. Circumferential variation due to forging cannot be erased by the machining process. Abstract: The Mechanisms of fatigue failure in Ti-6Al-2Sn-4Zr-6Mo forged discs are investigated: the effects of forging and machining operations on fatigue are decoupled. A four-point bend fatigue testing approach enabled the crack initiation and propagation characteristics to be studied at multiple locations around the disc periphery. Fatigue performance variation (of ~60%) at different positions, and crack initiation and propagation behaviour were linked to the heterogeneous crystallographic texture - developed during upstream forging. Downstream machining processes were found to increase fatigue life, regardless of the cutting speed. However, circumferential fatigue heterogeneity, inherent from the forging stage was still evident even after machining.